Prevalence and Molecular Characteristics of Avian-Origin mcr-1-Harboring Escherichia coli in Shandong Province, China - Zhao, Xiaonan; Liu, Zhengjie; Zhang, Yin; Yuan, Xiaomeng; Hu, Ming; Liu, Yuqing (Frontiers in Microbiology, 2020)
The objective of this study was to evaluate the prevalence and characteristics of avian-origin mcr-1-harbouring Escherichia coli in Shandong Province, China. During 2017-2018, a total of 668 nonduplicate E. coli isolates were separately collected from 8 large intensive poultry farms in Shandong Province. Antimicrobial susceptibility testing for 10 antimicrobial agents commonly used in farms was performed on all E. coli isolates by the agar dilution method; the mobile colistin resistance gene (mcr-1) gene was screened by PCR, and mcr-1 positive isolates were PCR-screened for antimicrobial resistance genes and typed by multi-locus sequence typing (MLST). Among the 668 E. coli, 102 (15.3%) harboured the mcr-1 gene; high antimicrobial resistance rates were observed for ampicillin (100/102, 98.0%), followed by amoxicillin (99/102, 97.1%) and florfenicol (97/102, 95.1%), and a low level of resistance was found for amoxicillin/clavulanic acid (24/102, 23.5%). Five ESBL genes were detected, and all isolates carried blaTEM (102/102, 100%), followed by blaCTX-M (90/102, 88.2%). Four PMQR genes were detected; aac(6)-Ib-cr (40/102, 39.2%) was the most commonly isolated PMQR gene, followed by qnrA (10/102, 9.8%). Thirty-eight different kinds of STs were identified, and the dominant ST was ST93 (19/102, 18.6%), followed by ST48 (9/102, 8.8%). In summary, E. coli from poultry in Shandong could be a reservoir for the mcr-1 gene, which could pose serious risks to human public health.